Role of Government Internal Supervisory Apparatus in Optimizing Performance Accountability of the Paser Regency Inspectorate - Nasrin, Mochamad; Aripin, Sofjan; Darmanto, Darmanto (PT. Riset Press International, 2023)
This research aims to analyze the role of Government Internal Oversight Apparatus in Optimizing Performance Accountability of the Paser Regency Inspectorate. The research used is descriptive qualitative research. In this descriptive qualitative research, it was carried out using a case study approach. In this research, researchers use case studies to analyze research findings, namely things that cause the role of the Government Internal Oversight Apparatus (APIP) as a consultant and as a catalyst/quality assurance (quality assurance) in realizing Inspectorate Performance Accountability is not optimal. The object of this research is the Government Internal Supervision Apparatus (APIP) at the Paser Regency Inspectorate. In this research, primary data was obtained directly from the research object through interviews with informants, namely some APIP elements at the Paser Regency Inspectorate. The main research instrument used in this research is the in-depth interview method. In this research, the triangulation used is data triangulation. The research findings show that APIP's competence is still inadequate in its role as a consultant so that it does not support the accountability of the Inspectorate's performance, APIP at the Paser Regency Inspectorate still cannot be said to be an agent of change and is still not optimal and still has shortcomings in carrying out its role as quality assurance. There are several things that must be done by all stakeholders, both leadership and organizational management levels, to improve the Inspectorate's Performance Accountability. Paser Regency in the future. There are several problems found in this research related to the performance accountability of the Paser Regency Inspectorate, and therefore it would be good if all stakeholders in the Paser Regency Inspectorate could correct these deficiencies, so that the performance accountability of the Paser Regency Inspectorate could be better